The effect of China's many-child policy on the number of births and the prevalence of serious teratogenic and disabling defects in Hunan Province - Donghua Xie; Jianhui Wei; Aihua Wang; Lili Xiong; Kehan Zou; Zhiqun Xie; Junqun Fang (BMC, 2023)
Abstract Background To research the effect of China's many-child policy on the number of births and the prevalence of serious teratogenic and disabling defects (STDDs) in Hunan province. Methods We performed an observational study based on the Birth Defect (BD) Surveillance System of Hunan Province and chose STDD case cards. From 2012-2022, we defined the following 4 periods: the one-child policy (OCP) (2012.01-2013.12), partial two-child policy (PTCP) (2014.1-2015.12), universal two-child policy (UTCP) (2016.1-2020.12), and the early stage of the three-child policy (ETCP) (2021.1-2022.12). Crude odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to examine the association of policy changes with STDDs. Crame'rʹs V was calculated to estimate the effect sizes. Joinpoint regression analysis and annual percent change (APC) were used for each segment of the trend. Results A total of 1,652,079 births were included in this analysis. Joinpoint regression analysis showed that the number of perinatal births increased from 2012 to 2017, with APC = 9.52 (95% CI: 7.2 to 11.8), and decreased from 2017 to 2022, with an APC = -10.04 (95% CI: -11.9 to -8.1). The number of mothers over 30 years old gradually increased, from 25.54% during the OCP period to 54.05% during the ETCP period (P trend < 0.001). With policy changes, the total prevalence of STDDs increased from 28.10 per 10,000 births during the period of OCP into 46.77 per 10,000 births during the ETCP period by 66.44%. The live birth prevalence of STDDs increased only during the ETCP period (PTCP: OR = 1.27, 95% CI: 0.99-1.24, p = 0.057, UTCP: OR = 1.22, 95% CI: 0.99-1.52, p = 0.067, ETCP: OR = 1.75, 95% CI: 1.37-2.24, p < 0.001). Over the past ten years, there was a decrease in the gestational age at diagnosis (*F = 772.520, p < 0.001), from 24.49 ± 5.65 weeks in 2012 to 20.77 ± 5.17 weeks in 2022. From 2012 to 2022, the percentage of deaths within 7 days decreased with APC = -18.85 (95% CI: -26.4- -10.5, P > 0.05). Conclusion Many-child policies were associated with a moderate increase in fertility especially for women in urban areas and older women. However, they have lost the ability to control birth since 2017. The total prevalence of STDDs increased over the entire period, but the live birth prevalence increased only during the ETCP period. The gestational age at diagnosis decreased and the percentage of deaths within 7 days decreased.